THE SEMANTIC NETWORK OF “HEAD” IN ENGLISH AND UZBEK BASED ON LEXICAL FIELD COMPARISON (Scientific journal of the Fergana State University, 2026)
This article presents a comparative lexical-semantic and discourse-pragmatic analysis of idioms with the component “head” in English and “bosh” in Uzbek. Idioms are classified into semantic fields such as cognition, emotion, and authority. Through lexical field theory, the study explores both universal and culture-specific imagery. The paper also examines the challenges of translating somatic idioms and their discourse functions. The findings contribute to bilingual lexicography, translation studies, and intercultural communication.